Impact of the investigation in maize improvement in Central America and the Caribbean: 1966-97. - López-Pereira, Miguel A. (2006)
Results of a CIMMYT study to determine the impacts of maize breeding research in Latin America in 1966-97 are presented, specifically in this case for Central America (Guatemala, El Salvador, Honduras, Nicaragua, Costa Rica, Panama) and the Caribbean (Cuba, Haiti, Dominican Republic). This study is part of a worldwide effort by CIMMYT to update a similar study done in 1992. Results are presented here on the number and characteristics of all the maize varieties and hybrids released by public research programs since 1966; investment in maize research by public and private organizations; the volume of maize seed sold in recent years, maize seed prices; maize area planted to improved seed and the estimated value of the surplus maize production due to the use of improved seed; and legal and regulatory aspects of maize seed industries in the region. The relationship between the national maize research programs and CIMMYT is also addressed especially how these organizations have worked together over the years to advance the knowledge and the development of new improved maize technologies.